31/#204 Cost-effectiveness of hysterectomy at the time of risk-reducing bilateral salpingooophorectomy for patients with BRCA1 mutations. (4th December 2022) - Dioun, Shayan; Chen, Ling; Gockley, Allison; Melamed, Alexander; Clair, Caryn St; Hou, June; Khoury-Collado, Fady; Elkin, Elena; Hershman, Dawn; Wright, Jason
Abstract : Objectives: More recent data suggests that patients with BRCA1 are at an increased risk of developing uterine serous cancers. This raises the question of whether a hysterectomy should be done at time of rrBSO. We developed a decision model to compare the cost-effectiveness of rrBSO with or without hysterectomy for patients with BRCA1 mutations. Methods: A Markov model was created to simulate the clinical trajectory of a hypothetical cohort of 10, 000 women aged 40 years of age with BRCA1 mutations undergoing rrBSO. The initial decision point in the model was whether a hysterectomy was performed at the time of rrBSO. A time horizon of 60 years was used. Postoperative morbidity and mortality were included in the model as well as risk for subsequent hysterectomy and prolapse after hysterectomy. Model probabilities, cost and utility values were derived with assumptions drawn from published literature. The effectiveness was calculated in terms of average quality adjusted life years (QALYs). The primary outcome was incremental cost-effectiveness ratios (ICERs), expressed in 2018 US dollars/QALYs. One way sensitivity analyses were performed to vary the assumptions across a range of plausible values. Results: RrBSO with hysterectomy was the least costly strategy at $13, 628, followed by rrBSO alone ($14, 630). Hysterectomy at time of rrBSO was cost-effective compared with rrBSO. rrBSO alone was subjected to absolute dominance because it was both more costly and less effective. Multiple one-way sensitivity analyses did not substantially impact the cost-effectiveness. Conclusions: Hysterectomy at time of rrBSO for BRCA1 patients constitutes a cost-effective management strategy.